THE INNOVATION AND ANTIOXIDANT ACTIVITY TEST OF DURIAN (DURIO ZIBENTHINUS M.) PEEL -OFF MASK - ananda magfirah sultan; Ervianingsih Ervianingsih; Syamsinar Idham; Nur Qhabilah Anastasya (Jurnal Endurance, 2023)
Indonesian society still uses plants for traditional medicine, and durian fruit is one example that is used as a traditional remedy (Durio zibethinus M.). The skin of durian fruit (Durio zibethinus M.) contains compounds such as alkaloids, tannins, saponins, and steroids. The results of antioxidant activity tests show that at a concentration of 1%, the skin of durian fruit has a strong antioxidant effect. This research was conducted to test the effectiveness of antioxidants in Peel-Off masks using durian fruit skin extract, as well as to find new innovations in the use of natural ingredients in skin care products. The innovation of Peel-Off masks made from durian fruit skin (Durio zibethinus M.) containing antioxidants can inhibit free radicals and also serve as an anti-aging agent, moisturizing and smoothing the skin. The technique used to determine the level of antioxidant effectiveness is UV Vis spectrophotometry at a wavelength of 516.2 nm with Vitamin C as the positive control, thus obtaining results to calculate the IC50 and AAI values of a sample. The results of this study obtained an IC50 value of 6.912 ppm and an AAI value of 23.148 for the durian fruit skin sample. For the Vitamin C sample, an IC50 value of 2.620 ppm and an AAI value of 61.071 were obtained. These results indicate that the durian fruit skin (Durio zibethinus M.) is a very strong antioxidant because the IC50 value is less than 50 (IC50 <50).